Diagnostic Accuracy of Adult-Assisting Hand Assessment in People with Chronic Stroke Who Had Pain - Seyed Hossein Hosseini; Ghorban Taghizade; Akram Azad (Shiraz University of Medical Sciences, 2022)
Background: Pain in patients with stroke is one of the essential factors that caninfluence upper-limb performance, and it is better to divide these people intoseparate groups. The Adult-Assisting Hand Assessment (Ad-AHA) is a tool thatrecently is being used in upper-limb performance evaluation among patientswith stroke. The present study aimed to evaluate the diagnostic accuracy of theAd-AHA among patients with chronic stroke who had pain to discriminatebetween the high upper-limb performance group and the low upper-limbperformance group.Methods: In this cross-sectional study, 51 patients (mean age±SD = 69.33±8.73)with chronic stroke who had pain participated and were divided into two groupsof high (group 1) and low (group 2) upper-limb performance measured bythe Action Reach Arm Test. The best cutoff point between groups, sensitivity,and specificity by receiver operating characteristic (ROC) for Ad-AHA wascalculated.Results: A significant difference in the total score of Ad-AHA between thehigh and low upper-limb performance groups was seen (P˂0.001). The bestcutoff point for the total score of Ad-AHA between stroke patients with highand low performance in the upper-limb who had pain was 47 (sensitivity=95.45,specificity=89.21).Conclusion: The results of this study show that the Ad-AHA has high sensitivityand specificity to discriminate between stroke patients with high and lowperformance in upper-limb performance who had pain.